The life of Hugo the horse - Wright, Anna Maria Rose, 1890-; Woodruff, Claude W. (New York, Grosset & Dunlap, 1935)
The birth and coming-of-age of a farm horse from the horse's point of view.
Keywords: Horses -- Fiction